Analyses of structural and electrical properties of aluminium doped ZnO-NPs by experimental and mathematical approaches - Mahmood Arslan; Munir Tariq; Fakhar-E-Alam M; Atif Muhammad; Shahzad Kaleem; Alimgeer K. S.; Nguyen Gia Tuan; Ahmad Hijaz; Ahmad Shafiq (ELSEVIER, 2022)
Pure and aluminium doped ZnO-NPs were played the central role in every field of life due to extraordi-nary physical, chemical and electrical properties. The main objective of the present research was used to enhance the electrical conductivity and reduce the electrical resistivity of aluminium doped zinc oxide-NPs. Synthesis of pure and aluminium doped zinc oxide-NPs (Zn1-xAlxO) at x = 0, 2.5, 5, 7.5 and 10 wt% was carried out by co-precipitation method. The XRD results depicted that hexagonal wurtzite crystal structure and crystallite size in the range of 13-25 nm were calculated by using Debye-Scherrer's equa-tion. Likewise, the non-uniform, irregular and pore like surface morphology of the prepared NPs was evi-dent from SEM micrographs. Various functional groups (CH, CO, OH and ZnO) attached to the surface of aluminium doped zinc oxide-NPs were identified by FTIR analysis. The UV-VIS spectra also depicted a shift towards the blue region of the visible spectrum. In terms of electrical properties with the help of experimental and mathematical analyses of aluminum doped zinc oxide-NPs exhibited higher conductiv-ity (1.34 x 10(-6) to 1.43 x 10(-3) S/cm) and lower resistivity (5.46 x 10(5) to 6.99 x 10(2) Omega-cm). The present results suggest that the aluminum doped zinc oxide-NPs have been improved the structural and electrical properties which make it a good candidate for optoelectronic devices. (c) 2021 The Authors.
Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).